Synthesis of Pharmacologically Important 2-[ω-(4-Morpholinyl)Alkyloxy]-1H-Isoindole-1,3-(2H)-Diones - Mehta, Deepika; K. Baregama, Latif; Talesara, G.L. (Asian Journal of Chemistry, 2010)
Morpholine when stirred with 3-bromopropene and ω-bromoalkyloxyphthalimide separately gave N-allyl morpholine (XIV) and α-phthalimidoxy- ω-(4-morpholinyl)alkane (XII) respectively. XIV on bromination and subsequent treatment with 2-hydroxy-1H-isoindole-1,3- (2H)-diones gave bis-1,2-phthalimidoxy-3-(N-morpholinyl) propane (XVI). Some compounds were tested for antimicrobial activity.